An integrated decision analysis methodology based on IF-DEMATEL and IF-ELECTRE for personnel selection - KILIÇ, HÜSEYİN SELÇUK (ELSEVIER, 2020)
Due to its complex, time-demanding, and multifaceted structure, personnel selection is considered as a multi-criteria decision-making problem, the framework of which includes both qualitative and quantitative criteria. Although various techniques have been proposed to address this problem in various industries, a robust methodology that is capable of explicitly considering the presence of uncertainty/vagueness is still a necessity. Therefore, with this study, we propose an integrated methodology that leverages Decision Making Trial and Evaluation Laboratory (DEMATEL) and Elimination and Choice Expressing the Reality (ELECTRE) methods under Intuitionistic Fuzzy (IF) environment. Within the proposed methodology, firstly, the IF-DEMATEL method is employed to obtain the importance-weights of the elicited criteria, and then the IF-ELECTRE method is formulated and applied to rank the candidates based on cardinal and ordinal evaluations. To illustrate the viability of the proposed methodology, an application case is performed at an air-filter manufacturing company. Hence, this study aims to contribute to the theoretical and practical extent of the related literature by proposing and illustrating an integrated analytics methodology capable of addressing personnel selection decisions in complex and imprecise real-world scenarios.
Keywords: Business analytics; Group decision-making; IF-DEMATEL; IF-ELECTRE; Multicriteria decision-making (MCDM); Personnel selection; HYBRID MCDM APPROACH; FUZZY TOPSIS; MANAGER SELECTION; OUTRANKING METHODS; PROJECT MANAGERS; MAKING APPROACH; SUPPLY CHAIN; AHP; PERFORMANCE; SYSTEM